Overnight, room temperature hold of whole blood followed by 42‐day storage of red blood cells in additive solution‐7. Issue 3 (19th September 2014) - Dumont, Larry J.; Cancelas, Jose A.; Maes, Lou Ann; Rugg, Neeta; Whitley, Pamela; Herschel, Louise; Siegal, Alan H.; Szczepiorkowski, Zbigniew M.; Hess, John R.; Zia, Majid
<x xml:space="preserve">Abstract</x> Background Overnight, room temperature hold (ONH) of whole blood before component processing offers several benefits. This study evaluated the storage and in vivo recovery characteristics of ONH red blood cells (RBCs) stored in additive solution‐7 (AS‐7). Study Design and Methods We conducted a three‐center, three‐arm evaluation of a new blood collection system with AS‐7 compared to leukoreduced RBCs processed within 8 hours and stored in AS‐1 (control). Whole blood (500 ± 50 mL) from healthy research subjects (n = 240) was held at room temperature 0 to 2 hours, 6 to 8 hours, or ONH (18‐24 hr) before component processing and storage at 1 to 6°C. RBCs were evaluated on Days 42 and 56 with a panel of in vitro assays. Subsets of the AS‐7–stored RBCs were evaluated for 51Cr 24‐hour in vivo recovery and long‐term survival. Results Adenosine triphosphate (ATP) levels in ONH RBCs were not different than AS‐7 RBCs prepared within 8 hours. ATP was higher in the ONH group on Day 42 than control, and ATP was maintained in all AS‐7 groups through Day 56. ONH units had 0.36 ± 0.14% on Day 42 hemolysis (60/60 < 0.8%), and 0.54 ± 0.22% on Day 56 (10/60 > 0.8%, 2/60 > 1%). In vivo recoveries of stored RBCs were not different between the AS‐7 arms at 42 days (p = 0.16; 27/27 ONH units > 75%), but the Day 56 ONH was significantly less than ONH on Day 42 (p = 0.008; 7/28 < 75%). Conclusions Overnight hold of whole blood at room temperature before component processing meets current regulatory requirements when RBCs are stored up to 42 days in AS‐7.